Echocardiographic criteria of physiological left ventricular hypertrophy in combined strength- and endurance-trained athletes - Urhausen, A.; Monz, T.; Kindermann, W. (The International Journal of Cardiovascular Imaging, 1997)
In combined strength- and endurance-trained athletes who are showing both unusual large body dimensions as well as a high physical fitness, the dimensions of the 'athlete's heart' are expected to reach physiological limits. Therefore we investigated 75 male and 77 female competitive rowers by means of doppler-echocardiography. The absolute "critical" heart weight of 500 g was exceeded by 61% of the male and 10% of the female rowers. Maximal values of the left ventricular (LV) muscle mass were measured at 170 (men) and 133 (women) g.m-2 body surface area, respectively. The LV end-diastolic internal diameter was measured to be above the upper clinical limit of 55 mm in 55% of the male and 17% of the female rowers. A LV wall thickness of 13 and 12 mm was only exceeded by 3 male and 1 female athlete, respectively (maximal values: 14 and 12.5 mm). The LV wall/internal diameter ratio did not exceed 48-50%. The systolic LV function as well as ECG and blood pressure did not reveal any pathological finding, the diastolic LV function was always measured within the normal range. The LV wall thicknesses, internal diameter and hypertrophic index (relation between wall thickness and internal diameter) of the rowers were significantly higher than those of 62 non-endurance trained athletes (pairwise matched according to the body dimensions) and similar to 28 male 'pure' endurance athletes (pairwise matched according to the absolute heart volume). In conclusion, upper limits of echocardiographic volume measurements that are considered critical may be clearly exceeded by healthy strength-endurance trained athletes with simultaneously high body dimensions. The clinical limits, however, are still valid in subjects with a body mass up to approximately 70 kg. The LV wall thickness only exceptionally exceed the clinical limits. A specific influence of the strength elements in training on the LV hypertrophy had not be found.